THE SOUTH AFRICAN ACT REVISITED – SOME CONSTITUTIONAL AND POLITICAL REFLECTIONS ON LESSONS LEARNT FROM THE CENTENARY OF THE UNION OF SOUTH AFRICA IN 1910 - GE Devenish (Obiter, 2021)
Just over a hundred years ago South Africa became a politically united state governed by the South Africa Act of 1909, which constituted the first constitution for a territory comprised of the four erstwhile British colonies of the Cape of Good Hope, Natal, the Transvaal and the Orange River Colony. This article revisits this historic constitution and attempts to revaluate its cardinal characteristics in the light of our subsequent constitutional and political development. This article also examines the constitutional and political configuration of the South Africa Act and how it came into being through a so-called National Convention and the part played by the prominent politicians and role players of the day. It examines the constitutional precedents that were available at the time. The crucial issues relating to the nature of the state that was to be established and why a unitary model and not a federation was adopted,are explained. It also considers the vexed question of the franchise and how a compromise was reached in this regard. Other important issues on which decisions had to be taken such as, inter alia, language, native and Indians affairs, are examined and evaluated. The article attempts to address certain important constitutional and political lessons that can be learnt from such an evaluation.